Two new phragmalin-type limonoids from stems of Chukrasia tabularis. (March 2016) - Peng, Jun-Lin; Jun-Wang,; Kong, Fan-Dong; Liu, Zi-Qi; Wang, Pei; Gai, Cui-Juan; Jiang, Bei; Mei, Wen-li; Dai, Hao-fu
Graphical abstract: Highlights: Two new phragmalin-type limonoids were isolated from the stems of Chukrasia tabularis A. Juss. Compounds2, 3 and4 showed inhibitory activity against α-glucosidase. The α -glucosidase inhibitory activity in vitro of limonoids has not yet been reported before our research. Abstract: Phytochemical investigation on the stems of Chukrasia tabularis A. Juss led to the isolation of two new phragmalin-type limonoids and three known ones. The structures of the new compounds were elucidated as Chuklarisin A (1 ) and Chuklarisin B (2 ) by spectroscopic techniques (IR, HRESIMS, 1D and 2D NMR) and comparing with published data. All the compounds were evaluated for α-glucosidase inhibitory activity in vitro . Compounds2, 3, and4 exhibited inhibitory activity against α-glucosidase with IC50 values of 0.96, 0.03, and 0.53 mM, respectively (acarbose as positive control, IC50 0.95 mM).